Community-based natural resource management: The role of social capital in collaborative environmental management of tribal resources in KwaZulu-Natal, South Africa. Issue 6 (1st November 2016) - Musavengane, Regis; Simatele, Danny Mulala
ABSTRACT: Community-based natural resource management (CBNRM) has become an important tool in promoting environmental and ecological sustainability as well as improving community access to eco-system services. However, CBNRM has been criticised as a programme that is largely driven by initiatives which are exogenous to local communities, promoting the agenda of external actors. In view of this, there is now increased attention given to CBNRM programmes that are co-management driven and which seek the participation of all community stakeholders. Using existing literature and field-based data, this article explores the role of social capital in promoting the management of common pool resources in tribal areas of KwaZulu-Natal. It is argued that social capital can be a vehicle through which the accumulation of different forms of capital can be achieved and contribute to sustainable environmental management.